Pengaruh Massa Biosorben Terhadap Penyerapan Ion Logam Cu(II) Oleh Ekstrak Pektin dari Kulit Buah Kedondong (Spondias dulcis) - Elinda Fithriana; Trisna Kumala Sari; Indang Dewata; Desy Kurniawati; Romy Dwipa Yamesa Away (Periodic, 2023)
Several industrial activities such as fertilizer industry, mining, battery, electronics and machinery can cause heavy metal pollution and one of them is Cu(II) heavy metal. At high levels of metal concentrations of Cu(II) will be very dangerous for the environment and living things, so it is necessary to find a solution to overcome the problem of metal pollution of Cu(II) is. One method that can be used is the biosorption method. In this study, pectin extract from kedondong fruit peel was used as a biosorbent. This research was conducted to determine the optimum mass of biosorbent in the biosorption process. Then the pectin characterization was carried out the Fourier Transform Infra Red instrument, then the absorbed Cu(II) metal content was determined using the Atomic Absorption Spectroscopy instrument. From this study, the optimum mass of biosorbent was 0.1 gram with an absorption capacity of 2,940 mg/g.